Біоморфологічні особливості та перспективи використання у декоративному садівництві України меконопсиса камбрійського (Meconopsis cambrica (L.) Vig.) - Gorai, G.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2005)
The paper shows the results of the primary introductional test of the ornamental representative of Poppies family Meconopsis cambrica (L.) Vig in conditions of M.M. Grishko NBG of the NAS of Ukraine. Calendar terms of phenological phases and their duration are determined and the characteristics of the development of vegetative and generative structures of the given species are investigated. The parameters of seed efficiency and vitalities of pollen are calculated in the course of investigation of the reproductive biology aspects in cultural conditions. The success of introduction is estimated on the basis of the dates received. The perspectives of use Meconopsis cambrica in gardening in the Polissya and Forest-Steppe of Ukraine are designed.